Third time lucky? China's push to internationalise the renminbi - Alessia Amighini; Alicia García Herrero (Bruegel, 2023)
Western concerns that the renminbi could rival the dollar as an international currency contrast with underwhelming numbers in terms of global settlements in renminbi and with the experience of China's two main previous failed attempts to achieve renminbi internationalisation. However, China is moving towards a more realistic plan for renminbi internationalisation, focusing on China's strengths in trade and financing. China is now the main trading partner for a very large number of countries and has become a major creditor for a good part of the Global South. This, together with the increasingly frequent restrictions on the use of the dollar, is strengthening the renminbi. The cross-border use of the renminbi for trade settlements and financing (Chinese banks' overseas loans denominated in renminbi and official renminbi swap lines offered by the People's Bank of China) has been on the rise since 2022, coinciding with Russia's invasion of Ukraine and the related Western sanctions. The increase is notable considering that the renminbi has been depreciating since January 2023 and China's economic performance has been underwhelming. However, the use of the renminbi as investment currency has declined since 2022, in terms of both the share of foreign-exchange reserves denominated in renminbi and the share of Chinese onshore assets held by foreign investors. The current push is so far proving successful compared to previous attempts, but it remains hard to tell if China will succeed in this renewed attempt to internationalise its currency through use of its heavy weight among trading nations. Obvious constraints remain that could hold back full internationalisation of the renminbi, especially the absence of full capital account convertibility. Nevertheless, China's somewhat heterodox approach to internationalising its currency could succeed given the ongoing placing of restrictions on use of the dollar. How the dollar, the euro or the international monetary system may be further affected by the rise of the renminbi is a major policy question that must be explored further.
Keywords: 330